2022
DOI: 10.46421/entac.v19i1.1999
|View full text |Cite
|
Sign up to set email alerts
|

The covid-19 pandemic in relation to built environment design characteristics

Abstract: During the Covid-19 pandemic, the built environment impacted the health and safety of the population. In Brazil, the pandemic impacted the ways of life of families, through housing and neighbourhood designs. This research identified built environment design factors that impacted life during the pandemic. A Systematic Literature Review was carried out to evaluate the impacts of the pandemic on the built environment and identify recommendations and actions to reduce those impacts. As a result, we recommend chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, transformations may trigger pathologies and affect the health of these families Castro, 2022). External transformation impacts housing design and functionality (Bortoli;Villa, 2020).…”
Section: Housing Transformationmentioning
confidence: 99%
“…In addition, transformations may trigger pathologies and affect the health of these families Castro, 2022). External transformation impacts housing design and functionality (Bortoli;Villa, 2020).…”
Section: Housing Transformationmentioning
confidence: 99%
“…Quality of life and its components of social, health, economic and environmental conditions were analysed. The second study evaluated SCs in Brazilian SH with the need for transformations of units and surroundings during the Covid-19 pandemic (KOWALTOWSKI et al, 2021;KOWALTOWSKI;CASTRO, 2022). Another study categorised issues related to SH studies in general, and identified and assessed SH shortcomings, primarily in Brazil (MUIANGA;.…”
Section: Identification Of Potential Social Costsmentioning
confidence: 99%